Impact of India ASEAN FTA on employment in Indian manufacturing sector. (27th November 2020) - Sikdar, Chandrima; Nag, Biswajit
Domestic production in Indian manufacturing sector failed to generate adequate employment opportunities but jobs supported by exports from the sector has been on the rise. The current study examines the employment effect of India-ASEAN Free Trade Agreement (IAFTA) on Indian manufacturing sector. Of the different FTAs signed by India, IAFTA involves one of the largest trade volumes. Using CGE modelling framework of GTAP database the study conducts simulations by calibrating the trade liberalisation scenario as of 2018 between India and the ASEAN countries. IAFTA fetches employment growth in manufacturing. But the beneficiaries of this gain are the unskilled labour who benefit both in terms of greater employment and higher wages. Higher usage of unskilled labour in conjunction with increased imported inputs also fetches productivity gains for the country. However, skilled labour employment is hit. Overall impact of IAFTA on manufacturing sector remains positive due to increased trade and employment gains.